2019
DOI: 10.3892/etm.2019.7284
|View full text |Cite
|
Sign up to set email alerts
|

miR‑128‑3p inhibits glioma cell proliferation and differentiation by targeting NPTX1 through IRS‑1/PI3K/AKT signaling pathway

Abstract: It has been reported that glioma has a higher morbidity and mortality than other types of malignant brain tumor. While glioma has been extensively researched, the exact molecular mechanisms of its genesis and progression have remained to be fully elucidated. In order to explore a novel glioma-associated pathway which may represent a therapeutic target, 61 pairs of tumor tissues and adjacent normal tissues of glioma patients were collected and subjected to reverse-transcription quantitative polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 35 publications
(35 reference statements)
2
42
0
Order By: Relevance
“…For example, it was reported that miR-128-3p suppressed breast cancer progression by targeting LIM domain kinase 1(LIMK1) [68]. Furthermore, miR-128-3p was demonstrated to inhibit glioma cell proliferation and differentiation through the IRS-1/PI3K/AKT signaling pathway [69]. Exosome-transmitted miR-128-3p could also exert its anticancer effect by increasing the chemosensitivity of oxaliplatin-resistant colorectal cancer [70].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was reported that miR-128-3p suppressed breast cancer progression by targeting LIM domain kinase 1(LIMK1) [68]. Furthermore, miR-128-3p was demonstrated to inhibit glioma cell proliferation and differentiation through the IRS-1/PI3K/AKT signaling pathway [69]. Exosome-transmitted miR-128-3p could also exert its anticancer effect by increasing the chemosensitivity of oxaliplatin-resistant colorectal cancer [70].…”
Section: Discussionmentioning
confidence: 99%
“…Selenium could mitigate lPS-induced myocardial inflammation by modulating the mir-128-3p/p38MaPK-nF-κB pathway (31). mir-128-3p also functions as a tumor suppressor in human breast cancer (32), glioma (33) and hepatocellular carcinoma (34). in the present study, mir-128-3p interference aggravated lPS-mediated damage in HMec-1 cells, and abolished the Hulc knockdown-mediated reduction of apoptosis and expression levels of proinflammatory cytokines in LPS-treated HMEC-1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The above results imply that HOTTIP can be directly combined with miR‐128‐3p and considered as a ceRNA. Numerous studies in recent years have confirmed that miR‐128‐3p can inhibit cell proliferation level (Huang et al, ; Huo et al, ; Zhou et al, ). The current research pointed out that miR‐128‐3p expression in testicular samples from Hypo patients was notably increased.…”
Section: Discussionmentioning
confidence: 94%